2008
DOI: 10.1111/j.1526-4610.2007.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of Migraine‐ACT and MIDAS Questionnaires for Assessing Migraine Therapy

Abstract: These results suggest that the Migraine-ACT questionnaire can be used more reliably than the MIDAS questionnaire for detecting improvements in treatment of new and follow-up patients with migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…Migraine is a debilitating disorder, and proper use of acute medication has been demonstrated to reduce disability over time. 18 Several studies suggested that adequate acute treatment is associated with improved outcomes, [19][20][21][22] and inadequate treatment has been recognized as an important barrier to optimal health outcomes. 23,24 Although triptans are safe in appropriately selected patients, perceptions about safety influence the behavior of both doctors and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine is a debilitating disorder, and proper use of acute medication has been demonstrated to reduce disability over time. 18 Several studies suggested that adequate acute treatment is associated with improved outcomes, [19][20][21][22] and inadequate treatment has been recognized as an important barrier to optimal health outcomes. 23,24 Although triptans are safe in appropriately selected patients, perceptions about safety influence the behavior of both doctors and patients.…”
Section: Discussionmentioning
confidence: 99%
“…We believe this reflects a substantial rate of underuse for a class of treatments that are widely recognized as effective. As several studies have demonstrated that use of adequate acute therapies is associated with improved outcomes, 23‐26 undertreatment is a barrier to good outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The MIDAS has been used as an outcome measure in both observational studies and clinical trials. The MIDAS is sensitive to change over time . Controlled trials show that the MIDAS is sensitive to treatment effects in both episodic and chronic migraine …”
Section: Methodsmentioning
confidence: 99%